Ginger Extract Decreases Susceptibility to Dextran Sulfate Sodium-Induced Colitis in Mice Following Early Antibiotic Exposure - Zhou, Xinghong; Liu, Xiaoyu; He, Qiuxing; Wang, Ming; Lu, Hanqi; You, Yanting; Chen, Liqian; Cheng, Jingru; Li, Fei; Fu, Xiuqiong; Kwan, Hiu Yee; Zhou, Lin; et al. (Frontiers in Medicine, 2022)
Background: Intestinal microbial colonisation in early life plays a crucial role in immune development and mucosal homeostasis in later years. Antibiotic exposure in early life increases the risk of inflammatory bowel disease. Ginger acts like a prebiotic and has been used in traditional Chinese medicine for colitis. We investigated the protective effect of ginger against dextran sulfate sodium (DSS)-induced colitis in mice exposed to antibiotic in early years. Methods: A weaned mouse model exposed to azithromycin for two weeks was used to mimic antibiotic exposure in childhood among humans. A diet containing ginger extract was administered to mice for 4 weeks after antibiotic exposure. The susceptibility to DSS-induced colitis was evaluated in terms of weight loss, disease activity index (DAI) score, colon length, colitis biomarkers and intestinal barrier function. The gut microbiota was analyzed in terms of 16S rRNA levels. Results: Ginger extract prevented weight loss, colon shortening, inflammation, and intestinal barrier dysfunction in mice exposed to antibiotics in early life. Ginger increased the bacterial diversity and changed the abundance of bacterial belonging to family Peptococcaceae and Helicobacter species to modulate microbiota structure and composition adversely affected by early antibiotic exposure. Conclusion: Ginger has a protective effect in potentially decreasing the susceptibility to colitis in mice exposed to antibiotics early in life.